Training System for SNE Teachers at Elementary, Middle, and High Schools: A Qualitative Analysis of the Case Studies Content - Ou, Jieping; Tsuge, Masayoshi; Kumagai, Keiko; Sambai, Ami; Miyamoto, Shoko; Okazaki, Shinji; Noro, Fumiyuki; Kojima, Michio; Yoneda, Hiroki (Department of Special Education, 2024)
Conventional lecture-style training ends up being biased toward teaching basic theoretical knowledge, and some issues have been identified. Therefore, it is necessary to construct an effective training system that could be used by in-service teachers in actual teaching practice. This case study relates to the issues encountered in creating individualized teaching plans (ITP) and teaching practices for students with special education needs enrolled in regular schools. This study analyzed 10 cases by using the qualitative data analysis software MAXQDA. Consequently, a more positive and accurate study of the students’ conditions was conducted, and diverse opinions were elicited, including exchanges of relevant information and teaching materials and tools, which enabled the trainees to feel the training effects. In this study, practical and ongoing training was conducted mainly in coordination with university teaching staff specializing in special needs education (SNE). This enabled the trainees and participants to deepen their understanding of students with special education needs and formed the basis of the case studies. The importance of practical learning should be stressed in in-service teacher training and in the pre-service education of teachers in Japan, and school-based experiences should be considered as an addition to the theoretical base of the university training stage.